2021
DOI: 10.1177/13506501211052763
|View full text |Cite
|
Sign up to set email alerts
|

The influence of laser surface texture on the tribological properties of friction layer materials in ultrasound motors

Abstract: Ultrasonic motors are typically driven by the dry friction force between the rotor and the stator; the friction pairs’ high friction coefficient and low wear rate are two essential elements for improving the operational stability with longer service life. In this research article, high-precision microgroove arrays were manufactured on the surfaces of the stator and rotor of the TRUSM60 ultrasonic motor using laser machining. Dry friction and wear tests between the stator and the rotor were carried out with pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…When the tangential force increases to the limit friction force, the object will be at the moment of sliding, and there will be a trend of relative displacement between the contact points. The interaction of the material surface roughness peaks, especially the harder roughness peaks penetrate and cut the softer material to form a groove effect, resulting in the loss of sliding friction energy [24,25]. The function of sliding friction can be expressed as follows:…”
Section: Geological Distribution Along the Linementioning
confidence: 99%
“…When the tangential force increases to the limit friction force, the object will be at the moment of sliding, and there will be a trend of relative displacement between the contact points. The interaction of the material surface roughness peaks, especially the harder roughness peaks penetrate and cut the softer material to form a groove effect, resulting in the loss of sliding friction energy [24,25]. The function of sliding friction can be expressed as follows:…”
Section: Geological Distribution Along the Linementioning
confidence: 99%
“…Nowadays, Laser Surface Texturing (LST), has become a well-known surface to improve the tribological characteristics of contact interface. Researchers have carried out a great deal of research on the tribological behaviour related to LST [13][14][15][16][17][18]. However, these studies are all carried out in the case of no current input, and the research related to LST under current-carrying condition is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have shown that the friction properties of micro-grooves are largely influenced by groove geometry. If the geometrical characteristics of the surface texture are not designed properly, it will not only be unable to improve the friction and wear of material surfaces but will even cause more severe friction and wear on the surface than non-textured surfaces [22][23][24][25]. Segu et al [26] developed multi-shape laser surface textured steel surfaces to improve the friction and wear performance under dry and lubrication conditions.…”
Section: Introductionmentioning
confidence: 99%